Isolation and characterization of human periodontal ligament stem cells under the terms of use in clinical application: A pilot study - Parichehr Behfarnia; Sheida Fazlalizadeh; Mohammad Hossein Nasr-Esfahani; Fatemeh Ejeian; Ahmad Mogharehabed (Wolters Kluwer Medknow Publications, 2023)
Background: The aim of the present study is to determine the possibility of isolation and characterization of the human periodontal ligament stem cells (hPDLSCs) using limited harvested periodontal ligament (PDL) tissue of only one patient's wisdom teeth (2-4 teeth) under the more compatible terms of use in clinical application without using the fetal bovine serum (FBS). Materials and Methods: In this pilot study, hPDLSCs were isolated from the impacted third molar, and tissue was scraped from the roots of the impacted third molar of 10 volunteers to enzymatically digest using collagenase. The cells were sub-cultured. The samples of the first seven patients and half of the eighth patient's sample were cultured in alpha modified of Eagle's medium (α-MEM) (−FBS) medium and the other part of the eighth patient's sample was cultured with prior medium supplemented with +FBS 15% as a control of the cultivation protocol. While for the past two patients (9th and 10th the α-MEM medium was supplemented with L-Glutamine, anti/anti 2X, and 20% knock-out serum replacement (KSR). Two more nutritious supplements (N2 and B27) were added to the medium of the tenth sample. Flow-cytometric analysis for the mesenchymal stem cell surface markers CD105, CD45, CD90, and CD73 was performed. Subsequent polymerase chain reaction was undertaken on three samples cultured with two growth media. Results: Cultivation failed in some of the samples because of the lack of cell adhesion to the culturing dish bottom (floating cells), but it was successful for the 9th and 10th patients, which were cultured in the α-MEM serum supplemented with KSR 20%. Flow cytometry analysis was positive for CD105, CD90, and CD73 and negative for CD45. The PDL stem cells (PDLSCs) expressed CD105, CD45, and CD90 but were poor for CD73. Conclusion: According to the limited number of sample tests in this study, isolation and characterization of PDLSCs from collected PDL tissue of one patient's wisdom teeth (2-4) may be possible by the proper setup in synthetic FBS-free serum.